Maternal activation of gap genes in the hover fly Episyrphus - Lemke, Steffen; Busch, Stephanie; Antonopoulos, Dionysos; Meyer, Folker; Domanus, Marc H.; Schmidt-Ott, Urs (Developmental biology, 2010)
The metameric organization of the insect body plan is initiated with the activation of gap genes, a set of transcription-factor-encoding genes that are zygotically expressed in broad and partially overlapping domains along the anteroposterior (AP) axis of the early embryo. The spatial pattern of gap gene expression domains along the AP axis is generally conserved, but the maternal genes that regulate their expression are not. Building on the comprehensive knowledge of maternal gap gene activation in Drosophila, we used loss- and gain-of-function experiments in the hover fly Episyrphus balteatus (Syrphidae) to address the question of how the maternal regulation of gap genes evolved. We find that, in Episyrphus, a highly diverged bicoid ortholog is solely responsible for the AP polarity of the embryo. Episyrphus bicoid represses anterior zygotic expression of caudal and activates the anterior and central gap genes orthodenticle, hunchback and Krüppel. In bicoid-deficient Episyrphus embryos, nanos is insufficient to generate morphological asymmetry along the AP axis. Furthermore, we find that torso transiently regulates anterior repression of caudal and is required for the activation of orthodenticle, whereas all posterior gap gene domains of knirps, giant, hunchback, tailless and huckebein depend on caudal. We conclude that all maternal coordinate genes have altered their specific functions during the radiation of higher flies (Cyclorrhapha).